Facile synthesis and electrochemical evaluation of PANI/CNT/MoS2 ternary composite as an electrode material for high performance supercapacitor - Thakur, A.K.; Deshmukh, A. B.; Choudhary, R. B.; Karbhal, I.; Majumder, M.; Shelke, M.V. (Materials Science and Engineering B: Solid-State Materials for Advanced Technology, 2017)
Synthesis of a novel ternary composite consisting of polyaniline (PANI), functionalized multi-walled carbon nanotubes (CNTs) and molybdenum disulfide (MoS2), via an in-situ polymerization method is reported. Detailed structural and electrochemical characterization shows that incorporation of a small amount of MoS2 in PANI/CNT composite tends to eliminate agglomeration problem of CNT. The PANI/CNT/MoS2 ternary composite reaches a specific capacitance of 350 F/g at the current density 1 A/g corresponding to a 5% MoS2 content. This ternary composite shows good cycling stability even at a higher energy density of 10 A/g. Further, PANI/CNT/MoS2 composite electrode shows higher energy density (7.77 Wh/kg) and power density (2140 W/kg) as compared to PANI/CNT composite without MoS2.
Keywords: MoS2; polyaniline; supercapacitor; Ternary Composite